The Real Plan: Stabilization and destabilization - Cinquetti, Carlos A. [UNESP] (Elsevier, 2000)
The paper analyzes Brazil's Real Plan, an exchange-rate based stabilization program, implemented in 1994, which mixed a spectacular price stabilization with some serious macroeconomic destabilization. The paper focuses on two of these imbalances: the consumption boom and the financial destabilization; showing that the former represented nothing the reverse side of a collapsed investment boom, which, in turn, led to the financial (banking) crisis. We hold that these instabilities were produced by a policy arrangement in which monetary and fiscal policies alone had to compensate for a largely appreciated, almost fixed, exchange rate anchor. (C) 2000 Elsevier Science Ltd. All rights reserved.
Keywords: Brazil; Consumption boom; Exchange rate anchor; Inflation; Real Plan; Stabilization program; exchange rate; fiscal policy; monetary policy; pricing policy; stabilization